A dimensão social da visualidade no fazer do historiador (TEL Tempo, Espaço e Linguagem, 2021)
This article interages with researches that discuss about the field of visuality as an important aspect of social life and social processes. It shows some perspective of cultural History and visual culture as favorable paths for news investigations by using images and it suggests as these vertentes can auxiliate historians in more adequate use of these visual materials. This way, the appropriate use of images can auxiliate the construction of a more plural and omnibus History.